Wykorzystanie etnografii wielomiejscowej w badaniach procesów migracji edukacyjnej wśród mniejszości litewskiej w Polsce = The use of multiplace etnography in the research on educational migration processes among the lithuanian minority in Poland - Wójcikowska, Katarzyna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article discusses the use of methodological strategy inspired by multiplace ethnography (Marcus 1995) in the research on migration of the Lithuanian minority from the borderland of Suwalki to the centres of the mother country and the state of permanent residence. The first part of the article sums the prevailing trends in the research on national minorities in Poland including the Lithuanian minority.
Keywords: etnografia; etnografia wielomiejscowa; migracje; mniejszość litewska; Polska